IFRS 9 and procyclicality of loan loss provision among Chinese regional banks, the role of local leaders’ turnover - Jiannan Yu; Maizatulakma Abdullah; Hamezah Md Nor (PLoS ONE, 2025)
This research aims to investigate the impact of IFRS 9 adoption on the procyclicality and the role of the local leaders’ turnover in this relationship. The financial accelerator theory and institutional theory provide a theoretical basis for this research. Using the panel data of 175 Chinese regional commercial banks from 2019–2022, this research estimates fixed-effects regression models to compare the procyclicality under IAS 39 and IFRS 9. The results reveal that the adoption of IFRS 9 mitigated procyclicality. This provides additional empirical evidence to the mixed results of prior studies, which were based on European countries. Further, the result also indicates that the local leaders’ turnover hinders the countercyclical effect of IFRS 9. This suggests that despite IFRS 9 helping alleviate procyclicality, the presence of local leaders’ turnover impedes achieving the countercyclical objective. These results highlight the importance of stable local leadership to the countercyclical function of IFRS 9. This research extends the geographical scope of research on IFRS 9. It is the first research that investigates the relationship between IFRS 9 adoption and the procyclicality in a non-Euro country. This research also provides insights into the interplay between IFRS 9, procyclicality, and local leaders’ turnover, and reveals the effect of political institutions on accounting practice. Additionally, this research contributes to the financial accelerator theory and institutional theory by extending their application into the accounting field. Based on these findings, this research recommends measures to enhance policy continuity during political transitions, strengthen forward-looking data infrastructure, improve supervisory oversight of discretionary provisioning, and tailor prudential policies.